Rapid Detection of Campylobacter jejuni in Poultry Products Using Quantum Dots and Nanobeads Based Fluorescent Immunoassay - Wang , Hong; Li, Yanbin; Slavik, Michael (International Journal of Poultry Science, 2014)
Campylobacter jejuni causes 2.1 to 2.4 million cases of foodborne illnesses in the United States each year with some of the cases linked to eating undercooked poultry or handling raw poultry and poultry products. Thus, a rapid, specific method is needed to detect C. jejuni on poultry and poultry products. The objective of this research was to develop a sensitive immunoassay method for rapid detection of C. jejuni by using both magnetic nanobeads to separate and concentrate the target bacteria and quantum dots (QDs) as fluorescent markers. In this research, both streptavidin conjugated QDs 620 (8 nm diameter) and magnetic nanobeads (150 nm diameter) were separately coated with the specific biotin conjugated anti-C. jejuni antibody. The conjugated magnetic nanobeads then were mixed with a sample containing C. jejuni. After immunomagnetic separation, the magnetic nanobeads-C. jejuni conjugates were mixed with the conjugated QDs. Then, unattached conjugated QDs were removed using immunomagnetic separation. A spectrometer was used to measure the fluorescence of the complexes of magnetic beads-C. jejuni-QDs. The results showed that this method could detect C. jejuni in pure culture, ground turkey, chicken juice or chicken carcass wash solution at concentrations down to 2-3 cells/0.1 mL sample (20-30 cfu/mL). The total detection time was less than 2 h. This study would provide the poultry industry a more effective rapid method for detection of major foodborne pathogens in poultry products to ensure food safety.